Recognition algorithm of non punctured polarization codes based on structural characteristics of coding matrix - Yao WANG; Xiang WANG; Guodong YANG; Zhitao HUANG (Tongxin xuebao)
In order to solve the problems of complexity and poor error adaptability in the blind recognition of standard non-punctured polarization codes, the theorems and propositions that could characterize the relationship between the code length and code rate, and distinguish information subchannel and frozen subchannel were proved.Based on the theorem and proposition, an efficient blind recognition algorithm was proposed.The proposed algorithm only needed to set the possible maximum code length, and the corresponding soft decision codewords matrixes and Kronecker matrixes were constructed.Based on the theorem and proposition proved, the check relationship between the two matrices was judged and the code rate and frozen bit position were estimated.The average likelihood difference was introduced as the test quantity, and the decision threshold was determined based on its theoretical probability distribution and minimax criterion.The simulation results show that the deduced theorem and propositions are consistent with the simulation results.Under the signal-to-noise ratio of 6 dB and code length of 1 024, the parameter recognition rate is still close to 100%.The recognition performance and computational complexity are better than the existing soft decision algorithms.